Talent management and its influence on organizational performance: A phenomenological study in information technology companies - Nugroho, Ageng; Wulandhari, Otti (Institute of Computer Science (IOCS), 2025)
This study explores talent management in information technology companies through a phenomenological approach with secondary data sources. The purpose of the study is to analyze talent management practices, identify key factors for their success, and evaluate their influence on organizational performance. The research method uses systematic literature study with interpretive qualitative analysis of the latest academic data sources. The results reveal the complexity of talent management in the digital era, which includes talent identification, development, and retention strategies. The findings show that the success of talent management depends on organizational structural factors, innovation culture, transformational leadership, and technological infrastructure. This research makes a theoretical contribution in understanding the dynamics of talent management and its practical implications for information technology organizations.